Advances in the Global Distribution, Chemical Constituents, and Pharmacology of Hippocampus, a Traditional Marine Chinese Medicine - Cui, Xinhai; Zhao, Xiangfeng; Li, Jintong; Li, Ziwei; Ren, Xia; Zhao, Yangang; Fu, Xianjun; Li, Xiuxue (Frontiers in Marine Science, 2021)
Hippocampus is an important traditional marine Chinese medicinal resource that has been used to warm and tonify kidney yang in the clinic for a long time in China. Modern pharmacological studies show that its active ingredients display a wide range of pharmacological activities associated with the kidney, such as anti-inflammation, antioxidation, antitumor, and neuroprotective effects. Herein, we systematically summarize and analyze the research progress on the resource distribution, active ingredients, pharmacological activities, and clinical application of Hippocampus. First, the species and worldwide distribution of Hippocampus were assessed to clarify the existing resources, and the results showed that 44 species of Hippocampus have been found in 159 countries and regions worldwide. Then, based on the analysis of 16 kinds of active ingredients and extraction methods, the relationship between the ingredient extraction and pharmacological activities of Hippocampus was revealed. This review may provide a foundation for further research on the potential active ingredients and mechanisms of Hippocampus. In addition, the research status of traditional prescriptions containing Hippocampus was evaluated. The results implied that research on Hippocampus is still in its infancy, and the mechanism and material basis of its efficacy have not been clarified. This paper should provide directions for further studies on Hippocampus.